2014
DOI: 10.1590/s0080-6234201400005000002
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mortality in infants with low birth weigh

Abstract: Objective To evaluate the factors associated with neonatal mortality in infant born with low birth weight. Method Cross-sectional study that analyzed data from 771 live births with low birth weight (<2500 g) in the city of Cuiabá, MT, in 2010, of whom 54 died in the neonatal period. We obtained data from the Information System on Live Births and Mortality, by integrated linkage. Results In multiple logistic regression, neonatal mortality was associated with: number of prenatal visits less than 7 (OR=3.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 26 publications
6
26
0
16
Order By: Relevance
“…20 In our study mortality rate was found to be increasing with decreasing birth weight and gestational age. Similar findings were noted in the study done by Sohely Y et al and Gavia M et al 21,22 In culture positive neonatal deaths gram negative organism were seen in majority which was in concordance to study done by Lim WH et al and Kalpana KL. 11,13 So, to conclude, neonatal sepsis is a well-recognized cause of neonatal mortality and morbidity and more pronounced in VLBW infants.…”
Section: Discussionsupporting
confidence: 90%
“…20 In our study mortality rate was found to be increasing with decreasing birth weight and gestational age. Similar findings were noted in the study done by Sohely Y et al and Gavia M et al 21,22 In culture positive neonatal deaths gram negative organism were seen in majority which was in concordance to study done by Lim WH et al and Kalpana KL. 11,13 So, to conclude, neonatal sepsis is a well-recognized cause of neonatal mortality and morbidity and more pronounced in VLBW infants.…”
Section: Discussionsupporting
confidence: 90%
“…O baixo peso ao nascer é citado como fator de maior influência na determinação da morbimortalidade infantil (11) , sendo considerado o principal preditor isolado da mortalidade infantil e neonatal (16) , existindo inclusive, uma relação inversamente proporcional entre mortalidade e peso ao nascer, em que a probabilidade de morte diminui à medida que o peso aumenta (10) . Neste estudo, a grande parte dos óbitos foi em RN com peso abaixo de 2.500 gramas, corroborando com estudo de Foz do Iguaçu (PR) (14) , no qual crianças nascidas com peso menor de 2.500g possuem maior risco de óbito (OR=17,9).…”
Section: Discussionunclassified
“…Entre os RN de muito baixo pesomenos de 1.500g -e os com 2.500g ou mais, possuem risco de morte 30 vezes maior. Além do mais, os recém-nascidos com extremo baixo peso (peso menor 1.000g) possuem risco de óbito 4,8 vezes maior em relação aos com peso entre 1.000g a 1.499g (10) .…”
Section: Discussionunclassified
“…Outro fator que está relacionado ao grande número de óbitos neonatais é a ausência ou insuficiência no número de consultas de pré-natal (20) , relacionados à qualidade do atendimento da equipe de saúde, e que estas estejam preparadas para o atendimento na reanimação cardiopulmonar em sala de parto, visando à prevenção da asfixia e/ou anóxia perinatal, sendo essa prática um importante mecanismo para reduzir a mortalidade neonatal (21) .…”
Section: Discussionunclassified